Assessment of Atmospheric Reanalyses With Independent Observations in the Weddell Sea, the Antarctic - Jonassen, Marius O; Välisuo, Ilona; Vihma, Timo; Uotila, Petteri; Makshtas, Alexander P; Launiainen, Jouko (Journal of Geophysical Research: Atmospheres, 2019)
Surface layer and upper-air in situ observations from two research vessel cruises and an ice station in the Weddell Sea from 1992 and 1996 are used to validate four current atmospheric reanalysis products: ERA-Interim, CFSR, JRA-55, and MERRA-2. Three of the observation data sets were not available for assimilation, providing a rare opportunity to validate the reanalyses in the otherwise datasparse region of the Antarctic against independent data. All four reanalyses produce 2 m temperatures warmer than the observations, and the biases vary from +2.0 K in CFSR to +2.8 K in MERRA-2. All four reanalyses are generally too warm also higher up in the atmospheric boundary layer (ABL), with biases up to +1.4 K (ERA-Interim). Cloud fractions are relatively poorly reproduced by the reanalyses, MERRA-2 and JRA-55 having the strongest positive and negative biases of about +30 % and −17 %, respectively. Skill scores of the error statistics reveal that ERA-Interim compares generally the most favorably against both the surface layer and the upper-air observations. CFSR compares the second best and JRA-55 and MERRA-2 have the least favorable scores. The ABL warm bias is consistent with previous evaluation studies in high latitudes, where more recent observations have been applied. As the amount of observations has varied depending on the decade, season, and region, the consistency of the warm bias suggests a need to improve the modeling systems, including data assimilation as well as ABL and surface parameterizations.
Keywords: Sørishavet; Weddellhavet; atmosfæren; geofysikk; meteorologi; observasjoner

Review of The life of José María Sobral: scientist, diarist, and pioneer in Antarctica, by Mary R. Tahan (2018). Cham, Switzerland: Springer International Publishing. 336 pp. ISBN 978-3-319-67267-0 - Millar, Pat (Polar Research, 2019)
Keywords: Antarktis; Otto Nordenskjöld; bokanmeldelser; dagbøker; ekspedisjoner; geodesi; magnetisme; meteorologi; oppdagelsesreiser

Very Strong Atmospheric Methane Growth in the 4 Years 2014–2017: Implications for the Paris Agreement - Nisbet, Euan G; Manning, Martin; Dlugokencky, Ed; Fisher, Rebecca; Lowry, Dave; Michel, Sylvia; Myhre, Cathrine Lund; Platt, Stephen Matthew; Allen, Grant; Bousquet, Philippe; Brownlow, Rebecca; Cain, Michelle; et al. (Global Biogeochemical Cycles, 2019)
Atmospheric methane grew very rapidly in 2014 (12.7 ± 0.5 ppb/year), 2015 (10.1 ± 0.7 ppb/year), 2016 (7.0 ± 0.7 ppb/year), and 2017 (7.7 ± 0.7 ppb/year), at rates not observed since the 1980s. The increase in the methane burden began in 2007, with the mean global mole fraction in remote surface background air rising from about 1,775 ppb in 2006 to 1,850 ppb in 2017. Simultaneously the 13C/12C isotopic ratio (expressed as δ13CCH4) has shifted, now trending negative for more than a decade. The causes of methane's recent mole fraction increase are therefore either a change in the relative proportions (and totals) of emissions from biogenic and thermogenic and pyrogenic sources, especially in the tropics and subtropics, or a decline in the atmospheric sink of methane, or both. Unfortunately, with limited measurement data sets, it is not currently possible to be more definitive. The climate warming impact of the observed methane increase over the past decade, if continued at >5 ppb/year in the coming decades, is sufficient to challenge the Paris Agreement, which requires sharp cuts in the atmospheric methane burden. However, anthropogenic methane emissions are relatively very large and thus offer attractive targets for rapid reduction, which are essential if the Paris Agreement aims are to be attained.
Keywords: Antarktis; atmosfæren; atmosfærisk metan; fossilt brensel; global klimamodell; global oppvarming; klimaendringer; klimagasser; metanisotoper; metanutslipp; meteorologi; polarområdene

Surface heat budget in the Southern Ocean from 42°S to the Antarctic marginal ice zone: four atmospheric reanalyses versus icebreaker Aurora Australis measurements - Yu, Lisan; Jin, Xiangze; Schulz, Eric W (Polar Research, 2019)
Surface heat fluxes from four atmospheric reanalyses in the Southern Ocean are evaluated using air–sea measurements obtained from the Aurora Australis during off-winter seasons in 2010–12. The icebreaker tracked between Hobart, Tasmania (ca. 42°S), and the Antarctic continent, providing in situ benchmarks for the surface energy budget change in the Subantarctic Southern Ocean (58–42°S) and the eastern Antarctic marginal ice zone (MIZ, 68–58°S). We find that the reanalyses show a high-level agreement among themselves, but this agreement reflects a universal bias, not a “truth.” Downward shortwave radiation (SW↓) is overestimated (warm biased) and downward longwave radiation (LW↓) is underestimated (cold biased), an indication that the cloud amount in all models is too low. The ocean surface in both regimes shows a heat gain from the atmosphere when averaged over the seven months (October–April). However, the ocean heat gain in reanalyses is overestimated by 10–36 W m−2 (80–220%) in the MIZ but underestimated by 6–20 W m−2 (7–25%) in the Subantarctic. The biases in SW↓ and LW↓ cancel out each other in the MIZ, causing the surface heat budget to be dictated by the underestimation bias in sensible heat loss. These reanalyses biases affect the surface energy budget in the Southern Ocean by meaningfully affecting the timing of the seasonal transition from net heat gain to net heat loss at the surface and the relative strength of SW↓ at different regimes in summer, when the length-of-day effect can lead to increased SW↓ at high latitudes.
Keywords: Sørishavet; havis; klima; meteorologi; oseanografi

Verification and Improvement of the Ability of CFSv2 to Predict the Antarctic Oscillation in Boreal Spring - Zhang, Dapeng; Huang, Yanyan; Sun, Bo; Li, Fei; Wang, Huijun (Advances in Atmospheric Sciences, 2019)
The boreal spring Antarctic Oscillation (AAO) has a significant impact on the spring and summer climate in China. This study evaluates the capability of the NCEP’s Climate Forecast System, version 2 (CFSv2), in predicting the boreal spring AAO for the period 1983–2015. The results indicate that CFSv2 has poor skill in predicting the spring AAO, failing to predict the zonally symmetric spatial pattern of the AAO, with an insignificant correlation of 0.02 between the predicted and observed AAO Index (AAOI). Considering the interannual increment approach can amplify the prediction signals, we firstly establish a dynamical–statistical model to improve the interannual increment of the AAOI (DY AAOI), with two predictors of CFSv2-forecasted concurrent spring sea surface temperatures and observed preceding autumn sea ice. This dynamical–statistical model demonstrates good capability in predicting DY AAOI, with a significant correlation coefficient of 0.58 between the observation and prediction during 1983–2015 in the two-year-out cross-validation. Then, we obtain an improved AAOI by adding the improved DY AAOI to the preceding observed AAOI. The improved AAOI shows a significant correlation coefficient of 0.45 with the observed AAOI during 1983–2015. Moreover, the unrealistic atmospheric response to March–April–May sea ice in CFSv2 may be the possible cause for the failure of CFSv2 to predict the AAO. This study gives new clues regarding AAO prediction and short-term climate prediction.
Keywords: Antarktis; atmosfæren; klimatologi; meteorologi

Contextualizing the 1997 warm event observed at Patriot Hills in the interior of West Antarctica - Carrasco, Jorge F (Polar Research, 2018)
Between 5 and 8 December 1997, the surface air temperature increased up to 3°C in the interior of West Antarctica, at Patriot Hills (PH), located at about 80°08’S, 81°16ʹ W, at an elevation of 855 m a.s.l. This was about 15°C warmer than the mean air temperature (−12°C) for this location at this time of the year. The ice surface field along the hills used as a runway for large aircraft melted, forming small ponds at the foot of the slope. This warm event was associated with a passing mid-tropospheric ridge that reached the interior of West Antarctica, whose anticyclonic circulation advected warm air towards the PH area. The foehn effect of the descending airflow on the northern slope of PH did not significantly contribute to the warming. The El Niño–Southern Oscillation (ENSO) was reaching its mature phase during the last quarter of 1997 and the warming/melting episode may be related to large-scale circulation associated with ENSO occurrence. However, warm events in the interior of West Antarctica may occur during any phase of ENSO. In contrast, the negative phase of the Antarctic Oscillation seems to support the development of the mid-tropospheric ridges that can advect warm maritime air towards the interior of West Antarctica. The 3°C registered at PH may be one of the highest near-surface air temperatures measured below 2500 m a.s.l. in the far interior coastal area of West Antarctica. This suggests a new subregion for determining air temperature records in Antarctica may need to be considered.
Keywords: Antarktis; føhn; føn; lufttemperatur; meteorologi; oppvarming; smelting; snø; sørlig oscillasjon

On the long-ignored scientific achievements of the Belgica expedition 1897–1899 - De Deckker, Patrick (Polar Research, 2018)
The Belgica expedition, which left Belgium in August 1897, was the first to spend 13 months continuously in Antarctic waters, before returning in late 1899. This was not only an exploratory venture, as new lands and oceans were charted, but more importantly it was an exceptional and successful scientific voyage. After the return of the expedition, a vast array of scientific data was processed and eventually 92 publications in some nine volumes funded by the Belgica Commission appeared over 40 years as a series called Résultats du voyage de la Belgica en 1897–99 sous le commandement de A. de Gerlache de Gomery – rapports scientifiques. Disappointingly, those significant results have been mostly ignored in the scientific literature and the paper here aims to inform scientists of the achievements of the Belgica expedition and where to obtain the information. Many of the climatological and oceanographic data obtained by the expeditioners ought to be examined in line with the changes that are occurring today in the Antarctic Peninsula region as a result of global warming. Some of the Belgica data form an important database to critically assess environmental changes over 120 years in the region of the Antarctic Peninsula.
Keywords: Antarktis; Belgica ekspedisjon; glasiologi; global oppvarming; klimaendringer; klimatologi; meteorologi; miljøendringer; oppdagelsesreiser; oseanografi; vitenskap

A hut too far: history of the Argentine Ventimiglia shelter on Peter I Øy - Fontana, Pablo Gabriel (Polar Research, 2018)
This paper addresses the barely known history of an Argentine Antarctic hut: the Teniente Luis Ventimiglia hut, installed by the Argentine Antarctic Institute on Peter I Øy (Peter I Island) in March 1971. In examining the history of the only Argentine Antarctic facility outside of the Argentine Antarctic Sector, this article describes the reasons behind the establishment of the hut and the scientific work that took place there as well as previous Argentine expeditions to Peter I.
Keywords: Argentina; Peter I. Øy; ekspedisjoner; forskningsstasjoner; meteorologi; oseanografi

The relationship between coastal weather and foraging behaviour of chinstrap penguins, Pygoscelis antarctica - Lowther, Andrew D; Trathan, Phil; Tarroux, Arnaud; Lydersen, Christian; Kovacs, Kit M (ICES Journal of Marine Science, 2018)
There is increasing interest in using higher-trophic level predators as ecosystem indicators because their performance is presumed to be linked to the overall function of the ecosystem that supports them. In the southwest Atlantic sector of the Southern Ocean, Antarctic krill (Euphausia superba) supports huge predator populations as well as a growing commercial fishery. To utilize information from the ecosystem in an adaptive framework for sustainably managing krill catch levels, performance indices of krill predators have been proposed as a proxy for krill abundance. However, there are several potentially confounding sources of variability that might impact predator performance such as the effects of environmental variability and fishing pressure on krill availability at scales relevant to predators. In this context, our study capitalises on the occurrence of an unexpected El Niño event to characterise how environmental variability can drive changes in predator foraging behaviour. We demonstrate a clear link between coastal downwelling and changes in the at-sea habitat usage of chinstrap penguins (Pygoscelis antarctica) foraging in a local krill fishing area. Penguins tracked from their breeding colonies on Powell Island, Antarctic Peninsula, undertook fewer, longer foraging trips during the downwelling-affected season compared with the season where no such downwelling was detected, suggesting that changes in climate-driven oceanography may have reduced krill availability along the northern shelf of the island. Our study demonstrates that penguin foraging behaviour is modified by scale-dependent processes, which if not accounted for may result in erroneous conclusions being drawn when using penguins as bioindicators of krill abundance.
Keywords: Sørishavet; marinbiologi; meteorologi; ornitologi; pingviner; økologi

Observations of Ice Nucleating Particles Over Southern Ocean Waters - McCluskey, Christina S; Hill, Thomas C J; Humphries, Ruhi S; Rauker, Anne M; Moreau, Sebastien; Strutton, P G; Chambers, Scott Dudley; Williams, Alastair G; McRobert, I; Ward, J; Keywood, Melita D; Harnwell, J; et al. (Geophysical Research Letters, 2018)
A likely important feature of the poorly understood aerosol-cloud interactions over the Southern Ocean (SO) is the dominant role of sea spray aerosol, versus terrestrial aerosol. Ice nucleating particles (INPs), or particles required for heterogeneous ice nucleation, present over the SO have not been studied in several decades. In this study, boundary layer aerosol properties and immersion freezing INP number concentrations (nINPs) were measured during a ship campaign that occurred south of Australia (down to 53°S) in March–April 2016. Ocean surface chlorophyll a concentrations ranged from 0.11 to 1.77 mg/m3, and nINPs were a factor of 100 lower than historical surveys, ranging from 0.38 to 4.6 m−3 at −20 °C. The INP population included organic heat-stable material, with contributions from heat-labile material. Lower INP source potentials of SO seawater samples compared to Arctic seawater were consistent with lower ice nucleating site densities in this study compared to north Atlantic air masses.
Keywords: Sørishavet; atmosfæren; iskjerner; iskrystaller; klimatologi; marin organisk aerosol; meteorologi; skyer

Mesospheric Nitric Acid Enhancements During Energetic Electron Precipitation Events Simulated by WACCM-D - Orsolini, Yvan J.; Smith-Johnsen, Christine; Marsh, Daniel R.; Stordal, Frode; Rodger, Craig J.; Verronen, Pekka T.; Clilverd, Mark A. (Journal of Geophysical Research: Atmospheres, 2018)
While observed mesospheric polar nitric acid enhancements have been attributed to energetic particle precipitation through ion cluster chemistry in the past, this phenomenon is not reproduced in current whole-atmosphere chemistry-climate models. We investigate such nitric acid enhancements resulting from energetic electron precipitation events using a recently developed variant of the Whole Atmosphere Community Climate Model (WACCM) that includes a sophisticated ion chemistry tailored for the D-layer of the ionosphere (50–90 km), namely, WACCM-D. Using the specified dynamics mode, that is, nudging dynamics in the troposphere and stratosphere to meteorological reanalyses, we perform a 1-year-long simulation (July 2009–June 2010) and contrast WACCM-D with the standard WACCM. Both WACCM and WACCM-D simulations are performed with and without forcing from medium-to-high energy electron precipitation, allowing a better representation of the energetic electrons penetrating into the mesosphere. We demonstrate the effects of the strong particle precipitation events which occurred during April and May 2010 on nitric acid and on key ion cluster species, as well as other relevant species of the nitrogen family. The 1-year-long simulation allows the event-related changes in neutral and ionic species to be placed in the context of their annual cycle. We especially highlight the role played by medium-to-high energy electrons in triggering ion cluster chemistry and ion-ion recombinations in the mesosphere and lower thermosphere during the precipitation event, leading to enhanced production of nitric acid and raising its abundance by 2 orders of magnitude from 10−4 to a few 10−2 ppb.
Keywords: Antarktis; elektroner; energiske partikler; geomagnetiske stormer; geovitenskap; ionosfæren; klimamodeller; meteorologi; polarområdene; salpetersyre; stratosfæren

Influence of meteorological parameters on atmospheric CO2 at Bharati, the Indian Antarctic research station - Pathakoti, Mahesh; Gaddamidi, Sreenivas; Gharai, Biswadip; Sudhakaran Syamala, Prijith; Venkata Narasimha Rao, Pamaraju; Choudhury, Saroj Bandh; Venkata Raghavendra, Kaila; Dadhwal, Vinay Kumar (Polar Research, 2018)
During the 35th Indian Scientific Expedition to Antarctica, measurements of atmospheric carbon dioxide (CO 2 ) were carried out using a Li-Cor CO 2 /H 2 O analyser at Bharati, the Indian Antarctic research station. This study examines the short-term variability of atmospheric CO 2 during the austral summer (January–February) of 2016. An average of 396.25 ± 4.20 ppm was observed during the study period. Meteorological parameters such as relative humidity, precipitation, wind speed, air temperature and atmospheric boundary layer height in conjunction with photosynthetically active radiation, the biological activity indicator which modulates atmospheric CO 2 concentration have been investigated. High wind speed (>20 m s −1 ) combined with precipitation scavenges CO 2 in the atmosphere, resulting in low concentrations at the study site. The lowest CO 2 concentration of 385 ppm coincided with heavy precipitation of 15 mm during study period. Statistical analysis of the data shows that precipitation and relative humidity independently correlated 55% (r = −0.55) and 32% (r = −0.32), respectively, with the variability of CO 2 mixing in the atmosphere at the study site. Atmospheric CO 2 was significantly correlated with precipitation alone with a p value of 0.003. Further, multiple regression analysis was performed to test the significant relation between variability of atmospheric CO 2 and meteorological parameters. Long-range air-mass transport analysis depicted that the majority of the air masses are reaching the study site through the oceanic region.
Keywords: Antarktis; atmosfæren; drivhuseffekt; drivhusgasser; forskning; karbondioksid; klimagasser; luftmassetransport; meteorologi; nedbør; polarområdene

Interhemispheric Survey of Polar Cap Aurora - Reidy, Jade; Fear, Robert; Whiter, Daniel; Lanchester, Betty; Kavanagh, Andrew John; Milan, Steve; Carter, Jennifer; Paxton, Larry; Zhang, Yongliang (Journal of Geophysical Research: Space Physics, 2018)
This study investigates the interhemispheric nature of polar cap auroras via ultraviolet imaging, combined with particle data, to determine whether they occur on open or closed field lines. Data from the SSUSI (Special Sensor Ultraviolet Spectrographic Imager) instrument on board the DMSP (Defence Meteorological Satellite Program) spacecraft are examined. The DMSP spacecraft are in 90-min orbits; hence, images of each hemisphere are separated by 45 min providing a good opportunity for interhemispheric study. 21 polar cap arc (PCA) events are recorded in December 2015 which have particle data from the SSJ/4 particle spectrometer associated with an arc in at least one hemisphere. Nine events are found to contain 'arcs' consistent with a closed field line mechanism, that is, arcs associated with an ion signature present in both hemispheres. Six events contained arcs that were consistent with an 'open field line' mechanism, that is, they were associated with electron-only precipitation. Events containing arcs that were not consistent with either of these expectations are also explored, including an example of a 'non-conjugate' theta aurora and an interesting example of auroral morphology similar to a PCA which is associated with a geomagnetic storm. Seasonal effects are also investigated through a statistical analysis of PCAs over 4 months in 2015. It is found that PCAs are visible in the SSUSI data at least 20% of the time and that it is likely some are missed due to the spacecraft field of view and poor sensitivity in the summer hemisphere due to increased solar illumination.
Keywords: Antarktis; astronomi; energiske partikler; geomagnetiske stormer; meteorologi; polarlys; polarområdene; solvind

Precipitation instruments at Rothera Station, Antarctic Peninsula: a comparative study - Tang, Malcolm S Y; Nettukandy Chenoli, Sheeba; Colwell, Steve; Grant, Rosey; Simms, Mairi; Law, John; Abu Samaha, Azizan (Polar Research, 2018)
Direct measurement of precipitation in the Antarctic using ground-based instruments is important to validate the results from climate models, reanalyses and satellite observations. Quantifying precipitation in Antarctica faces many unique challenges such as wind and other technical difficulties due to the harsh environment. This study compares a variety of precipitation measurements in Antarctica, including satellite data and reanalysis fields at Rothera Station, Antarctica Peninsula. The tipping bucket gauges (TBGs) were less sensitive than laserbased sensors (LBSs). The most sensitive LBS (Visibility and Present Weather Sensor, VPF-730) registered 276 precipitation days, while the most sensitive TBG (Universal Precipitation Gauge, UPG-1000) detected 152 precipitation days. Case studies of the precipitation and seasonal accumulation results show the VPF-730 to be the most reliable precipitation sensor of the evaluated instruments. The precipitation amounts given by the reanalyses were positively correlated with wind speed. The precipitation from the Japanese 55-year Reanalysis was most affected by wind speed. Case studies also show that during low wind periods, precipitation measurements from the instruments were very close to the precipitation measurement given by the Global Precipitation Climatology Project (GPCP) 1-degreedaily (1DD) data. During strong wind events, the GPCP 1DD did not fully capture the effect of wind, accounting for the relatively small precipitation amount. The Laser Precipitation Monitor (LPM) and Campbell Scientific-700 (CS700H) experienced instrumental errors during the study, which caused the precipitation readings to become exceedingly high and low, respectively. Installing multiple LBSs in different locations (in close proximity) can help identify inconsistency in the readings.
Keywords: Antarktis; analyser; klimatologi; meteorologi; nedbør; satellitt observasjoner

Occurrence and average behavior of pulsating aurora - Partamies, Noora; Whiter, Daniel; Kadokura, Akira; Kauristie, Kirsti; Nesse Tyssøy, Hilde; Massetti, Stefano; Stauning, Peter; Raita, Tero (Journal of Geophysical Research: Space Physics, 2017)
Motivated by recent event studies and modeling efforts on pulsating aurora, which conclude that the precipitation energy during these events is high enough to cause significant chemical changes in the mesosphere, this study looks for the bulk behavior of auroral pulsations. Based on about 400 pulsating aurora events, we outline the typical duration, geomagnetic conditions, and change in the peak emission height for the events. We show that the auroral peak emission height for both green and blue emission decreases by about 8 km at the start of the pulsating aurora interval. This brings the hardest 10% of the electrons down to about 90 km altitude. The median duration of pulsating aurora is about 1.4 h. This value is a conservative estimate since in many cases the end of event is limited by the end of auroral imaging for the night or the aurora drifting out of the camera field of view. The longest durations of auroral pulsations are observed during events which start within the substorm recovery phases. As a result, the geomagnetic indices are not able to describe pulsating aurora. Simultaneous Antarctic auroral images were found for 10 pulsating aurora events. In eight cases auroral pulsations were seen in the southern hemispheric data as well, suggesting an equatorial precipitation source and a frequent interhemispheric occurrence. The long lifetimes of pulsating aurora, their interhemispheric occurrence, and the relatively high-precipitation energies make this type of aurora an effective energy deposition process which is easy to identify from the ground-based image data.
Keywords: Antarktis; astronomi; atmosfæren; geofysikk; geomagnetiske stormer; mesosfæren; meteorologi; polarlys

Observation-Based Trends of the Southern Ocean Carbon Sink - Ritter, Rebecca; Landschützer, Peter; Gruber, Nicolas; Fay, Amanda R; Iida, Yosuke; Jones, Stephen Daniel; Nakaoka, Shin-ichiro; Park, Geun-Ha; Peylin, Philippe; Rödenbeck, Christian; Rodgers, Keith B; Shutler, Jamie D; et al. (Geophysical Research Letters, 2017)
The Southern Ocean (SO) carbon sink has strengthened substantially since the year 2000, following a decade of a weakening trend. However, the surface ocean pCO2 data underlying this trend reversal are sparse, requiring a substantial amount of extrapolation to map the data. Here we use nine different pCO2 mapping products to investigate the SO trends and their sensitivity to the mapping procedure. We find a robust temporal coherence for the entire SO, with eight of the nine products agreeing on the sign of the decadal trends, that is, a weakening CO2 sink trend in the 1990s (on average 0.22 ± 0.24 Pg C yr−1 decade−1), and a strengthening sink trend during the 2000s (−0.35 ± 0.23 Pg C yr−1 decade−1). Spatially, the multiproduct mean reveals rather uniform trends, but the confidence is limited, given the small number of statistically significant trends from the individual products, particularly during the data-sparse 1990–1999 period.
Keywords: Sørishavet; biogeokjemi; global oppvarming; karbondioksid; klimaendringer; klimatologi; meteorologi

On Roald Amundsen’s scientific achievements - Blix, Arnoldus Schytte (Polar Research, 2016)
This paper describes the significant direct and indirect contributions to science made by the Norwegian polar explorer Roald Amundsen in the period 1897–1924. It documents that his expeditions through the North-west Passage (1903–06) with Gjøa, to the South Pole (1910–12) with Fram and through the North-east Passage (1918–1920) and the Chukchi and East Siberian seas (1921–25) with Maud yielded vast amounts of published scientific material on meteorology, terrestrial magnetism, geology, palaeontology, oceanography, ethnography, zoology and botany, which, though celebrated at the time, have since received scant recognition in more recent assessments of Amundsen’s achievements. Keywords: Fridtjof Nansen; polar exploration; South Pole; North-west Passage; North-east Passage; H.U. Sverdrup.
Keywords: Antarktis; Roald Amundsen; Sydpolsekspedisjonen; ekspedisjoner; forskning; geologi; meteorologi; oseanografi

Re-assessment of recent (2008 - 2013) surface mass balance over Dome Argus, Antarctica - Ding, Minghu; Xiao, Cunde; Yang, Yuande; Wang, Yetang; Li, Chuanjin; Yuan, Naiming; Shi, Guitao; Sun, Weijun; Ming, Jing (Polar Research, 2016)
At Dome Argus, East Antarctica, the surface mass balance (SMB) from 2008 to 2013 was evaluated using 49 stakes installed across a 30×30 km area. Spatial analysis showed that at least 12 and 20 stakes are needed to obtain reliable estimates of SMB at local scales (a few hundred square metres) and regional scales (tens of square kilometres), respectively. The estimated annual mean SMB was 22.9±5.9 kg m−2 yr−1, including a net loss by sublimation of −2.22±0.02 kg m−2 yr−1 and a mass gain by deposition of 1.37±0.01 kg m−2 yr−1. Therefore, ca. 14.3% of precipitation was modified after deposition, which should be considered when interpreting snow or ice core records produced by future drilling projects. The surface snow density and SMB in the western portion of Dome Argus are higher than in other areas, and these differences are likely related to the katabatic wind, which is strengthened by topography in this sector. A new digital elevation model (DEM) of Dome Argus was generated, confirming that both peaks of the dome can be considered as the summit of the East Antarctic Ice Sheet. Findings from this study should be valuable for validating SMB estimates obtained from regional climate models and DEMs established using remote-sensing data. Keywords: Snow accumulation; Kunlun Station; CHINARE; digital elevation model; deep ice core sites; East Antarctic Ice Sheet.
Keywords: Antarktis; glasiologi; innlandsis; meteorologi; snø akkumulasjon; topografi

In memory of Torgny Vinje - a genuine polar scientist - Isaksson, Elisabeth; Gerland, Sebastian; Divine, Dmitry (Polar Research, 2016)
Keywords: Antarktis; Norsk Polarinstitutt; biografi; forskning; geofysikk; geologi; glasiologi; meteorologi; polarområdene

Evaluating CMIP5 ocean biogeochemistry and Southern Ocean carbon uptake using atmospheric potential oxygen: Present-day performance and future projection - Nevison, Cynthia; Manizza, Manfredi; Keeling, Ralph; Stephens, Britton; Bent, Jonathan; Dunne, John P; Ilyina, Tatiana; Long, Matthew; Resplandy, Laure; Tjiputra, Jerry; Yukimoto, Seiji (Geophysical Research Letters, 2016)
Observed seasonal cycles in atmospheric potential oxygen (APO ~ O2 + 1.1 CO2) were used to evaluate eight ocean biogeochemistry models from the Coupled Model Intercomparison Project (CMIP5). Model APO seasonal cycles were computed from the CMIP5 air-sea O2 and CO2 fluxes and compared to observations at three Southern Hemisphere monitoring sites. Four of the models captured either the observed APO seasonal amplitude or phasing relatively well, while the other four did not. Many models had an unrealistic seasonal phasing or amplitude of the CO2 flux, which in turn influenced APO. By 2100 under RCP8.5, the models projected little change in the O2 component of APO but large changes in the seasonality of the CO2 component associated with ocean acidification. The models with poorer performance on present-day APO tended to project larger net carbon uptake in the Southern Ocean, both today and in 2100.
Keywords: Sørishavet; atmosfæren; biogeokjemi; karbon syklus; karbondioksid; klimatologi; meteorologi; oseanografi

"Big Science" for meteorologene - Nilsen, Yngve; Vollset, Magnus (Vinden dreier : meteorologiens historie i Norge, 2016)
Keywords: Bouvetøya; ekspedisjoner; forskning; meteorologi

Advancements in decadal climate predictability: The role of nonoceanic drivers - Bellucci, Alessio; Haarsma, Rein; Bellouin, Nicolas; Booth, Ben B; Cagnazzo, Chiara; van den Hurk, Bart; Keenlyside, Noel; Koenigk, Torben; Massonnet, François; Materia, Stefano; Weiss, M (Reviews of Geophysics, 2015)
We review recent progress in understanding the role of sea ice, land surface, stratosphere, and aerosols in decadal-scale predictability and discuss the perspectives for improving the predictive capabilities of current Earth system models (ESMs). These constituents have received relatively little attention because their contribution to the slow climatic manifold is controversial in comparison to that of the large heat capacity of the oceans. Furthermore, their initialization as well as their representation in state-of-the-art climate models remains a challenge. Numerous extraoceanic processes that could be active over the decadal range are proposed. Potential predictability associated with the aforementioned, poorly represented, and scarcely observed constituents of the climate system has been primarily inspected through numerical simulations performed under idealized experimental settings. The impact, however, on practical decadal predictions, conducted with realistically initialized full-fledged climate models, is still largely unexploited. Enhancing initial-value predictability through an improved model initialization appears to be a viable option for land surface, sea ice, and, marginally, the stratosphere. Similarly, capturing future aerosol emission storylines might lead to an improved representation of both global and regional short-term climatic changes. In addition to these factors, a key role on the overall predictive ability of ESMs is expected to be played by an accurate representation of processes associated with specific components of the climate system. These act as “signal carriers,” transferring across the climatic phase space the information associated with the initial state and boundary forcings, and dynamically bridging different (otherwise unconnected) subsystems. Through this mechanism, Earth system components trigger low-frequency variability modes, thus extending the predictability beyond the seasonal scale.
Keywords: Sørishavet; geofysikk; havis; klimaendringer; klimamodeller; meteorologi; polarområdene; sjøis

Application of remotely piloted aircraft systems in observing the atmospheric boundary layer over Antarctic sea ice in winter - Jonassen, Marius O; Tisler, Priit; Altstädter, Barbara; Scholtz, Andreas; Vihma, Timo; Lampert, Astrid; König-Langlo, Gert; Lüpkes, Christof (Polar Research, 2015)
The main aim of this paper is to explore the potential of combining measurements from fixed- and rotary-wing remotely piloted aircraft systems (RPAS) to complement data sets from radio soundings as well as ship and sea-ice-based instrumentation for atmospheric boundary layer (ABL) profiling. This study represents a proof-of-concept of RPAS observations in the Antarctic sea-ice zone. We present first results from the RV Polarstern Antarctic winter expedition in the Weddell Sea in June–August 2013, during which three RPAS were operated to measure temperature, humidity and wind; a fixed-wing small unmanned meteorological observer (SUMO), a fixed-wing meteorological mini-aerial vehicle, and an advanced mission and operation research quadcopter. A total of 86 RPAS flights showed a strongly varying ABL structure ranging from slightly unstable temperature stratification near the surface to conditions with strong surface-based temperature inversions. The RPAS observations supplement the regular upper air soundings and standard meteorological measurements made during the campaign. The SUMO and quadcopter temperature profiles agree very well and, excluding cases with strong temperature inversions, 70% of the variance in the difference between the SUMO and quadcopter temperature profiles can be explained by natural, temporal, temperature fluctuations. Strong temperature inversions cause the largest differences, which are induced by SUMO’s high climb rates and slow sensor response. Under such conditions, the quadcopter, with its slower climb rate and faster sensor, is very useful in obtaining accurate temperature profiles in the lowest 100 m above the sea ice. Keywords: Remotely piloted aircraft systems; unmanned aerial vehicles; Weddell Sea; polar meteorology; Antarctic; boundary layer meteorology.
Keywords: Sørishavet; Weddellhavet; fjernstyrte flysystemer; havis; meteorologi; målinger; observasjoner; sjøis; ubemannede luftfartøyer

Observational evidence of the influence of Antarctic stratospheric ozone variability on middle atmosphere dynamics - Narukull, Venkateswara Rao; Espy, Patrick Joseph; Hibbins, Robert; Fritts, David C; Kavanagh, Andrew John (Geophysical Research Letters, 2015)
Abstract Modeling results have suggested that the circulation of the stratosphere and mesosphere in spring is strongly affected by the perturbations in heating induced by the Antarctic ozone hole. Here using both mesospheric MF radar wind observations from Rothera Antarctica (67°S, 68°W) as well as stratospheric analysis data, we present observational evidence that the stratospheric and mesospheric wind strengths are highly anti-correlated, and show their largest variability in November. We find that these changes are related to the total amount of ozone loss that occurs during the Antarctic spring ozone hole and particularly with the ozone gradients that develop between 57.5°S and 77.5°S. The results show that with increasing ozone loss during spring, winter conditions in the stratosphere and mesosphere persist longer into the summer. These results are discussed in the light of observations of the onset and duration of the Antarctic polar mesospheric cloud season.
Keywords: Antarktis; klimatologi; meteorologi; ozonhull; ozonlaget

Investigating the recent apparent hiatus in surface temperature increases: 2. Comparison of model ensembles to observational estimates - Thorne, Peter; Outten, Stephen; Bethke, Ingo; Seland, Øyvind (Journal of Geophysical Research: Atmospheres, 2015)
To assess published hypotheses surrounding the recent slowdown in surface warming (hiatus), we compare five available global observational surface temperature estimates to two 30-member ensembles from the Norwegian Earth System Model (NorESM). Model ensembles are initialized in 1980 from the transient historical runs and driven with forcings used in the CMIP5 experiments and updated forcings based upon current observational understanding, described in Part 1. The ensembles' surface temperature trends are statistically indistinguishable over 1998–2012 despite differences in the prescribed forcings. There is thus no evidence that forcing errors play a significant role in explaining the hiatus according to NorESM. The observations fall either toward the lower portion of the ensembles or, for some observational estimates and regions, outside. The exception is the Arctic where the observations fall toward the upper ensemble bounds. Observational data set choices can make a large difference to findings of consistency or otherwise. Those NorESM ensemble members that exhibit Nino3.4 Sea Surface Temperature (SST) trends similar to observed also exhibit comparable tropical and to some extent global mean trends, supporting a role for El Nino Southern Oscillation in explaining the hiatus. Several ensemble members capture the marked seasonality observed in Northern Hemisphere midlatitude trends, with cooling in the wintertime and warming in the remaining seasons. Overall, we find that we cannot falsify NorESM as being capable of explaining the observed hiatus behavior. Importantly, this is not equivalent to concluding NorESM could simultaneously capture all important facets of the hiatus. Similar experiments with further, distinct, Earth System Models are required to verify our findings.
Keywords: Antarktis; atmosfæren; fjernmåling; geofysikk; klimaendringer; klimatologi; meteorologi; observasjoner; polarområdene; temperatur

HFC-43-10mee atmospheric abundances and global emission estimates - Arnold, Tim; Ivy, Diane J; Harth, Christina M; Vollmer, Martin K; Mühle, Jens; Salameh, Peter K; Paul Steele, L; Krummel, Paul B; Wang, Ray H J; Young, Dickon; Lunder, Chris R; Hermansen, Ove; et al. (Geophysical Research Letters, 2014)
We report in situ atmospheric measurements of hydrofluorocarbon HFC-43-10mee (C5H2F10; 1,1,1,2,2,3,4,5,5,5-decafluoropentane) from seven observatories at various latitudes, together with measurements of archived air samples and recent Antarctic flask air samples. The global mean tropospheric abundance was 0.21 ± 0.05 ppt (parts per trillion, dry air mole fraction) in 2012, rising from 0.04 ± 0.03 ppt in 2000. We combine the measurements with a model and an inverse method to estimate rising global emissions—from 0.43 ± 0.34 Gg yr−1 in 2000 to 1.13 ± 0.31 Gg yr−1 in 2012 (~1.9 Tg CO2-eq yr−1 based on a 100 year global warming potential of 1660). HFC-43-10mee—a cleaning solvent used in the electronics industry—is currently a minor contributor to global radiative forcing relative to total HFCs; however, our calculated emissions highlight a significant difference from the available reported figures and projected estimates.
Keywords: Antarktis; atmosfæren; forurensning; massespektrometri; meteorologi; målinger; utslipp

Recent climate tendencies on an East Antarctic ice shelf inferred from a shallow firn core network - Schlosser, Elisabeth; Anschütz, Helgard; Divine, Dmitry; Martma, Tõnu; Sinisalo, Anna; Altnau, Sebastian; Isaksson, Elisabeth (Journal of Geophysical Research: Atmospheres, 2014)
Nearly three decades of stable isotope ratios and surface mass balance (SMB) data from eight shallow firn cores retrieved at Fimbul Ice Shelf, East Antarctica, in the Austral summers 2009–2011 have been investigated. An additional longer core drilled in 2000/2001 extends the series back to the early eighteenth century. Isotope ratios and SMB from the stacked record of all cores were also related to instrumental temperature data from Neumayer Station on Ekström Ice Shelf. Since the second half of the twentieth century, the SMB shows a statistically significant negative trend, whereas the δ18O of the cores shows a significant positive trend. No trend is found in air temperature at the nearest suitable weather station, Neumayer (available since 1981). This does not correspond to the statistically significant positive trend in Southern Annular Mode (SAM) index, which is usually associated with a cooling of East Antarctica. SAM index and SMB are negatively correlated, which might be explained by a decrease in meridional exchange of energy and moisture leading to lower precipitation amounts. Future monitoring of climate change on the sensitive Antarctic ice shelves is necessary to assess its consequences for sea level change.
Keywords: Antarktis; brehylle; geofysikk; geologi; glasiologi; havnivåstigning; isbrem; isshelf; klimaendringer; meteorologi; stabile isotoper

The influence of Nunataks on atmospheric boundary layer convection during summer in Dronning Maud Land, Antarctica - Stenmark, Aurora; Hole, Lars Robert; Voss, Paul; Reuder, Joachim; Jonassen, Marius O (Journal of Geophysical Research: Atmospheres, 2014)
The effects of nunataks on temperature profiles and wind patterns are studied using simulations from the Weather Research and Forecasting model. Simulations are compared to hourly observations from an automatic weather station located at the Troll Research Station in Dronning Maud Land. Areas of bare ground have been implemented in the model, and the simulations correspond well with meteorological measurements acquired during the 4 day simulation period. The nunataks are radiatively heated during daytime, and free convection occurs in the overlying atmospheric boundary layer. The inflow below the updraft forces strong horizontal convergence at the surface, whereas weaker divergence appears aloft. In a control run with a completely ice-covered surface, the convection is absent. In situ observations carried out by a remotely controlled balloon and a small model airplane compare well with model temperature profiles, but these are only available over the ice field upwind to the nunatak.
Keywords: Dronning Maud Land; atmosfæren; geofysikk; meteorologi; nunataker; observasjoner

Atmosphere–sea ice interaction in early summer in the Antarctic: evaluation and challenges of a regional atmospheric model - Valkonen, T.; Vihma, T.; Johansson, M. M.; Launiainen, J. (Quarterly Journal of the Royal Meteorological Society, 2014)
Antarctic sea ice areas have only been the main focus for a few studies combining observations and three-dimensional atmospheric model experiments. This study presents simulations over the Weddell Sea in early summer, applying the polar-optimized version of the Weather Research and Forecasting model (Polar WRF). The results are compared against observations from the drifting experiment Ice Station Polarstern, which took place on 28 November 2004?2 January 2005. The Polar WRF model showed good skill in simulating synoptic-scale variations. The diurnal cycles of surface variables were reproduced, but the amplitude was overestimated for most of the variables and the simulations were characterized by a cold temperature bias at night. The major challenges related to the modelling of the atmosphere over Antarctic sea ice were found to be associated with clouds, atmospheric boundary-layer processes and processes in the sea ice and snow layer. Temporal variations in the errors in cloud cover generated large errors in long-wave radiation fluxes. In the boundary layer, the overestimated downward sensible heat flux was partly compensated for by the underestimated downward long-wave radiation at the surface. The underestimated downward long-wave flux started to dominate as the stability increased and generated the cold temperature bias at the surface. Problems with the surface energy balance, as found in this study, could be reduced by applying more advanced schemes for snow and ice thermodynamics.
Publisher: John Wiley & Sons, Ltd
Keywords: Sørishavet; Weddellhavet; atmosfæren; havis; meteorologi; sjøis

Atmospheric trace elements in aerosols observed over the Southern Ocean and coastal East Antarctica - Xu, Guojie; Gao, Yuan (Polar Research, 2014)
Atmospheric aerosol samples were collected over the Southern Ocean (SO) and coastal East Antarctica (CEA) during the austral summer of 2010/11. Samples were analysed for trace elements, including Na, Mg, K, Al, Fe, Mn, Ni, Cd and Se, by inductively coupled plasma mass spectrometry (ICP-MS). The mean atmospheric concentrations over the SO were 1100 ng m−3 for Na, 190 ng m−3 for Mg, 150 ng m−3 for Al, 14 ng m−3 for Fe, 0.46 ng m−3 for Mn and 0.25 ng m−3 for Se. Over CEA, the mean concentrations were 990 ng m−3 for Na, 180 ng m−3 for Mg, 190 ng m−3 for Al, 26 ng m−3 for Fe, 0.70 ng m−3 for Mn and 0.29 ng m−3 for Se. Particle size distributions, enrichment factors (EFs) and correlation analysis indicate that Na, Mg and K mainly came from the marine source, while Al, Fe and Mn were mainly from the crustal source, which also contributed to Mg and K over CEA. High EFs were associated with Ni, Cd and Se, suggesting likely contributions from mixed sources from the Antarctic continent, long-range transport, marine biogenic emissions and anthropogenic emissions. Sea-salt elements (Na, Mg, K) were mainly accumulated in the coarse mode, and crustal elements (Al, Fe, Mn) presented a bimodal size distribution pattern. Bioactive elements (Fe, Ni, Cd) were enriched in the fine mode, especially with samples collected over the SO, possibly affecting biogeochemical cycles in this oceanic region. Keywords: Southern Ocean; coastal East Antarctica; trace elements; size distribution; sources.
Keywords: Sørishavet; atmosfærisk aerosol; biogeokjemi; kjemiske analyser; meteorologi

Assessing the potential of calcium-based artificial ocean alkalinization to mitigate rising atmospheric CO2 and ocean acidification - Ilyina, Tatiana; Wolf-Gladrow, Dieter; Munhoven, Guy; Heinze, Christoph (Geophysical Research Letters, 2013)
Enhancement of ocean alkalinity using calcium compounds, e.g., lime has been proposed to mitigate further increase of atmospheric CO2 and ocean acidification due to anthropogenic CO2 emissions. Using a global model, we show that such alkalinization has the potential to preserve pH and the saturation state of carbonate minerals at close to today's values. Effects of alkalinization persist after termination: Atmospheric CO2 and pH do not return to unmitigated levels. Only scenarios in which large amounts of alkalinity (i.e., in a ratio of 2:1 with respect to emitted CO2) are added over large ocean areas can boost oceanic CO2 uptake sufficiently to avoid further ocean acidification on the global scale, thereby elevating some key biogeochemical parameters, e.g., pH significantly above preindustrial levels. Smaller-scale alkalinization could counteract ocean acidification on a subregional or even local scale, e.g., in upwelling systems. The decrease of atmospheric CO2 would then be a small side effect.
Keywords: Sørishavet; biogeokjemi; havalkalisering; klimatologi; meteorologi; modeller

Observations of nitric oxide in the Antarctic middle atmosphere during recurrent geomagnetic storms - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Straub, Corinne; Holmén, Kim; Horne, Richard B (Journal of Geophysical Research: Space Physics, 2013)
We report ground-based measurements of the polar middle atmosphere made using a 230–250 GHz passive microwave radiometer deployed at Troll station (72°01′S 02°32′E, L shell of L = 4.8), Antarctica. Our observations show enhanced mesospheric nitric oxide (NO) volume mixing ratio (VMR) during a series of small recurrent geomagnetic storms in the 2008 austral winter, reaching 1.2 ppmv on day 200 (18 July). The Lomb normalized periodogram of the NO VMR time series averaged over 65-80 km for days 130 to 220 of 2008 (9 May to 7 August) shows a peak exceeding the 95% confidence limit at 25.8 days, close to the synodic rotation period for low-latitude solar coronal holes. The highest correlations between the radiometer NO VMR data and trapped and quasi-trapped electron count rates for L = 3.5-5.5 from the Polar Orbiting Environment Satellites 90° telescope are for the >30 keV (90e1) channel (rmax = 0.56, lag time of 5.1 days) and >100 keV (90e2) channel (rmax = 0.57, lag time of 4.4 days). Maximum correlation between NO VMR and the >700 keV (90P6) channel data is lower but lag times are close to zero. Superposed epoch analyses for the eight most significant geomagnetic storm periods and three Carrington rotations (2070-2072) within the 90 day observation period indicate that significant NO abundance observed at 65-80 km in the Antarctic mesosphere may be produced directly by >200 keV electron precipitation or originate from a source at higher altitudes, e.g., production by >30 keV electrons followed by downward transport.
Keywords: Antarktis; atmosfæren; fysikk; geomagnetiske stormer; meteorologi; polarområdene

Arctic and Antarctic sea ice acts as a sink for atmospheric CO2 during periods of snowmelt and surface flooding - Nomura, Daiki; Granskog, Mats A; Assmy, Philipp; Simizu, Daisuke; Hashida, Gen (Journal of Geophysical Research: Oceans, 2013)
In this study, we present evidence that Antarctic and Arctic sea ice act as sink for atmospheric CO2 during periods of snowmelt and surface flooding. The CO2 flux measured directly at the flooded sea ice surface (Fflood) constituted a net CO2 sink of −1.1 ± 0.9 mmol C m−2 d−1 (mean ± 1 SD), which was an order of magnitude higher than the flux measured at the snow-air surface (Fsnow) and bare ice surface (Fice). The Fsnow/Fflood ratio decreased with increasing water equivalent of snow and superimposed-ice, suggesting that the properties of snow and superimposed-ice formation affect the magnitude of the CO2 flux. The Fsnow/Fflood ratio ranged from 0.1 to 0.5, illustrating that 50–90% of the potential flux at the flooded surface was reduced due to the presence of snow/superimposed-ice. Hence, snow cover properties and superimposed-ice play an important role in the CO2 fluxes across the sea ice-snow-atmosphere interface.
Keywords: Sørishavet; atmosfæren; gassutveksling; havis; karbondioksid; klimaendringer; klimatologi; meteorologi; polarområdene; sjøis

Chemical composition of tropospheric air masses encountered during high altitude flights (>11.5 km) during the 2009 fall Operation Ice Bridge field campaign - Yang, Mei Ying Melissa; Vay, Stephanie A; Stohl, Andreas; Choi, Yonghoon; Diskin, Glenn S; Sachse, Glen W; Blake, Donald R (Journal of Geophysical Research: Atmospheres, 2012)
As part of the 2009 Operation Ice Bridge campaign, the NASA DC-8 aircraft was used to fill the data-time gap in laser observation of the changes in ice sheets, glaciers and sea ice between ICESat-I (Ice, Cloud, and land Elevation Satellite) and ICESat-II. Complementing the cryospheric instrument payload were four in situ atmospheric sampling instruments integrated onboard to measure trace gas concentrations of CO2, CO, N2O, CH4, water vapor and various VOCs (Volatile Organic Compounds). This paper examines two plumes encountered at high altitude (12 km) during the campaign; one during a southbound transit flight (13°S) and the other at 86°S over Antarctica. The data presented are especially significant as the Southern Hemisphere is heavily under-sampled during the austral spring, with few if any high-resolution airborne observations of atmospheric gases made over Antarctica. Strong enhancements of CO, CH4, N2O, CHCl3, OCS, C2H6, C2H2 and C3H8 were observed in the two intercepted air masses that exhibited variations in VOC composition suggesting different sources. The transport model FLEXPART showed that the 13°S plume contained predominately biomass burning emissions originating from Southeast Asia and South Africa, while both anthropogenic and biomass burning emissions were observed at 86°S with South America and South Africa as indicated source regions. The data presented here show evidence that boundary layer pollution is transported from lower latitudes toward the upper troposphere above the South Pole, which may not have been observed in the past.
Keywords: Antarktis; atmosfæren; atmosfæriske gasser; forurensning; havis; innlandsis; isbreer; isbrem; kjemi; kjemiske analyser; menneskelig påvirkning; meteorologi; sjøis; sporgass

A comparison of the present and last interglacial periods in six Antarctic ice cores - Masson-Delmotte, Valerie; Buiron, Daphné; Ekaykin, Alexey Anatolievich; Frezzotti, M; Gallée, Hubert; Jouzel, Jean; Krinner, Gerhard; Landais, Amaelle; Motoyama, Hideaki; Oerter, Hans; Pol, K; Pollard, D; et al. (Clim. Past, 2011)
We compare the present and last interglacial periods as recorded in Antarctic water stable isotope records now available at various temporal resolutions from six East Antarctic ice cores: Vostok, Taylor Dome, EPICA Dome C (EDC), EPICA Dronning Maud Land (EDML), Dome Fuji and the recent TALDICE ice core from Talos Dome. We first review the different modern site characteristics in terms of ice flow, meteorological conditions, precipitation intermittency and moisture origin, as depicted by meteorological data, atmospheric reanalyses and Lagrangian moisture source diagnostics. These different factors can indeed alter the relationships between temperature and water stable isotopes. Using five records with sufficient resolution on the EDC3 age scale, common features are quantified through principal component analyses. Consistent with instrumental records and atmospheric model results, the ice core data depict rather coherent and homogenous patterns in East Antarctica during the last two interglacials. Across the East Antarctic plateau, regional differences, with respect to the common East Antarctic signal, appear to have similar patterns during the current and last interglacials. We identify two abrupt shifts in isotopic records during the glacial inception at TALDICE and EDML, likely caused by regional sea ice expansion. These regional differences are discussed in terms of moisture origin and in terms of past changes in local elevation histories, which are compared to ice sheet model results. Our results suggest that elevation changes may contribute significantly to inter-site differences. These elevation changes may be underestimated by current ice sheet models.
Publisher: Copernicus Publications
Keywords: Antarktis; Dronning Maud Land; Sørishavet; atmosfæren; glasiologi; iskjerner; klimatologi; meteorologi; stabile isotoper

Direct observations of nitric oxide produced by energetic electron precipitation into the Antarctic middle atmosphere - Newnham, David A; Espy, Patrick J; Clilverd, Mark A; Rodger, Craig J; Seppälä, Annika; Maxfield, David J; Hartogh, Paul; Holmén, Kim; Horne, Richard B (Geophysical Research Letters, 2011)
We report the first ground-based passive microwave observations made from Troll station, Antarctica, which show enhanced mesospheric nitric oxide (NO) volume mixing ratio reaching levels of 1.2 ppmv, or 2–3 orders of magnitude above background, at 70–80 km during small, relatively isolated geomagnetic storms in 2008. The mesospheric NO peaked 2 days after enhanced NO at higher altitudes (110–150 km) measured by the SABER satellite, and 2 days after peaks in the >30 keV and >300 keV electron flux measured by POES, although the 300 keV electron flux remained high. High time resolution data shows that mesospheric NO was enhanced at night and decayed during the day and built up to high levels over a period of 3–4 days. The altitude profile of mesospheric NO suggests direct production by ∼300 keV electron precipitation. Simulations using the Sodankylä Ion and Neutral Chemistry model show that the delay between thermospheric and mesospheric NO enhancements was primarily a result of the weaker production rate at lower altitudes by ∼300 keV electrons competing against strong day-time losses.
Keywords: Dronning Maud Land; Troll forskningsstasjon; geofysikk; geomagnetiske stormer; meteorologi; observasjoner; radiometer

Using transport diagnostics to understand chemistry climate model ozone simulations - Strahan, Susan; Douglass, A R; Stolarski, R S; Akiyoshi, Hideharu; Bekki, Slimane; Braesicke, P; Butchart, N; Chipperfield, Martyn; Cugnet, David; Dhomse, Sandip; Frith, Stacey; Gettelman, Andrew; et al. (Journal of Geophysical Research: Atmospheres, 2011)
We use observations of N2O and mean age to identify realistic transport in models in order to explain their ozone predictions. The results are applied to 15 chemistry climate models (CCMs) participating in the 2010 World Meteorological Organization ozone assessment. Comparison of the observed and simulated N2O, mean age and their compact correlation identifies models with fast or slow circulations and reveals details of model ascent and tropical isolation. This process-oriented diagnostic is more useful than mean age alone because it identifies models with compensating transport deficiencies that produce fortuitous agreement with mean age. The diagnosed model transport behavior is related to a model's ability to produce realistic lower stratosphere (LS) O3 profiles. Models with the greatest tropical transport problems compare poorly with O3 observations. Models with the most realistic LS transport agree more closely with LS observations and each other. We incorporate the results of the chemistry evaluations in the Stratospheric Processes and their Role in Climate (SPARC) CCMVal Report to explain the range of CCM predictions for the return-to-1980 dates for global (60°S–60°N) and Antarctic column ozone. Antarctic O3 return dates are generally correlated with vortex Cly levels, and vortex Cly is generally correlated with the model's circulation, although model Cl chemistry and conservation problems also have a significant effect on return date. In both regions, models with good LS transport and chemistry produce a smaller range of predictions for the return-to-1980 ozone values. This study suggests that the current range of predicted return dates is unnecessarily broad due to identifiable model deficiencies.
Keywords: Antarktis; drivhusgasser; fysikk; geovitenskap; klimamodeller; meteorologi; ozonlaget; stratosfæren

Mesospheric wind semidiurnal tides within the Canadian Middle Atmosphere Model Data Assimilation System - Xu, Xiaoyong; Manson, Alan H; Meek, Christopher; Jacobi, Christoph; Hall, Chris; Drummond, James (Journal of Geophysical Research: Atmospheres, 2011)
The horizontal wind data from the standard version of Canadian Middle Atmosphere Model Data Assimilation System (CMAM-DAS) for the years 2006–2008 are analyzed to obtain the global structure and seasonal variability of the semidiurnal tide (SDT) in the mesosphere. The modeled amplitudes and phases of the SDTs at single stations from middle/high northern latitudes are quite similar to those observed by radars. The primary nonmigrating tides identified in both the meridional wind and zonal wind semidiurnal spectra at 88 km include the westward propagating wave numbers s = 1 (SW1), 3 (SW3), 4 (SW4), 6 (SW6), the standing s = 0 (S0), and the eastward propagating s = 2 (SE2). The migrating SDT (SW2) amplitude maxima usually occur at 40°N–60°N during December–February and August–September, and also at 40°S–60°S in April–May, with the dominance of (2, 4) during October–April and (2, 3) and (2, 5) dominance for other months. The CMAM-DAS is quite successful in reproducing the dominance of SW1 in the Antarctic summer mesosphere. The modeled SW1 shows very good overall agreement in both amplitude and phase with wind measurements from UARS High Resolution Doppler Imager and Wind Imaging Interferometer (UARS-HRDI/WINDII) and from TIMED Doppler Interferometer (TIDI). The CMAM-DAS analyses for SW3, SW4, SW6, and S0 are also in reasonable agreement with those determined from the HRDI/WINDII or TIDI wind measurements. This work provides further evidence for the tidal forcing from below.
Keywords: Antarktis; atmosfæren; atmosfærisk tidevann; geofysikk; meteorologi

An inter-comparison of six latent and sensible heat flux products over the Southern Ocean - Yu, Lejiang; Zhang, Zhanhai; Zhong, Shiyuan; Zhou, Mingyu; Gao, Zhiqiu; Wu, Huiding; Sun, Bo (Polar Research, 2011)
The latent heat fluxes (LHF) and sensible heat fluxes (SHF) over the Southern Ocean from six different data sets are inter-compared for the period 1988- 2000. The six data sets include three satellite-based products, namely, the second version of the Goddard Satellite-Based Surface Turbulent Fluxes data set (GSSTF-2), the third version of the Hamburg Ocean Atmosphere Parameters and Fluxes from Satellite Data (HOAPS-3) and the Japanese Ocean Fluxes Data Sets with Use of Remote Sensing Observations (J-OFURO); two global reanalysis products, namely, the National Centers for Environmental Prediction-Department of Energy Reanalysis 2 data set (NCEP-2) and the European Centre for Medium-Range Weather Forecasts 40 Year Re-analysis data set (ERA-40); and the Objectively Analyzed Air-Sea Fluxes for the Global Oceans data set (OAFlux). All these products reveal a similar pattern in the averaged flux fields. The zonal mean LHF fields all exhibit a continuous increase equatorward. With an exception of HOAPS-3, the zonal mean SHF fields display a minimum value near 50°S, increasing both pole- and equatorward. The differences in the standard deviation for LHF are larger among the six data products than the differences for SHF. Over the regions where the surface fluxes are significantly influenced by the Antarctic Oscillation and the Pacific-South American teleconnection, the values and distributions of both LHF and SHF are consistent among the six products. It was found that the spatial patterns of the standard deviations and trends of LHF and SHF can be explained primarily by sea-air specific humidity and temperature differences; wind speed plays a minor role. Keywords: Latent heat flux; sensible heat flux; Southern Ocean.
Keywords: Sørishavet; klimatologi; meteorologi; observasjoner

Evaluating CERES angular distribution models for snow using surface reflectance observations from the East Antarctic Plateau - Hudson, Stephen R; Kato, Seiji; Warren, Stephen G (Journal of Geophysical Research: Atmospheres, 2010)
Clouds and the Earth's radiant energy system (CERES) is a satellite-based remote sensing system designed to monitor the Earth's radiation budget. In this paper we examine uncertainties in the angular distribution models (ADMs) used by CERES over permanently snow covered surfaces with clear skies. These ADMs are a key part of the CERES data processing algorithms, used to convert the observed upwelling radiance to an estimate of the upwelling hemispheric flux. We model top-of-atmosphere anisotropic reflectance factors using an atmospheric radiative transfer model with a lower boundary condition based on extensive reflectance observations made at Dome C, Antarctica. The model results and subsequent analysis show that the CERES operational clear-sky permanent-snow ADMs are appropriate for use over Dome C, with differences of less than 5% between the model results and the ADMs at most geometries used by CERES operationally. We show that the uncertainty introduced into the flux estimates through the use of the modeled radiances used in the ADM development is small when the fluxes are averaged over time and space. Finally, we show that variations in the angular distribution of radiance at the top of the atmosphere due to atmospheric variability over permanently snow covered regions are in most cases unlikely to mask the real variations in flux caused by these atmospheric variations.
Keywords: Antarktis; atmosfæren; fjernmåling; klima; meteorologi; observasjoner; snø; solstråling

A comparison of shortwave reflectance over the East Antarctic Plateau observed by CERES to that estimated from surface reflectance observations - Hudson, Stephen R; Warren, Stephen G; Kato, Seiji (Journal of Geophysical Research: Atmospheres, 2010)
Spectral albedo and bidirectional reflectance of snow were measured at Dome C on the East Antarctic Plateau for wavelengths of 350–2400 nm and solar zenith angles of 52°–87°. A parameterization of bidirectional reflectance, based on those measurements, is used as the lower boundary condition in the atmospheric radiation model SBDART to calculate radiance and flux at the top of the atmosphere (TOA). The model's atmospheric profile is based on radiosoundings at Dome C and ozonesoundings at the South Pole. Computed TOA radiances are integrated over wavelength for comparison with the Clouds and the Earth's Radiant Energy System (CERES) shortwave channel. CERES radiance observations and flux estimates from four clear days in January 2004 and January 2005 from within 200 km of Dome C are compared with the TOA radiances and fluxes computed for the same solar zenith angle and viewing geometry, providing 11,000 comparisons. The measured radiance and flux are lower than the computed values. The median difference is about 7% for CERES on Terra, and 9% on Aqua. Sources of uncertainty in the model and observations are examined in detail and suggest that the measured values should be less than the computed values, but only by 1.7% ± 4%. The source of the discrepancy of about 6% cannot be identified here; however, the modeled values do agree with observations from another satellite instrument (Multiangle Imaging Spectroradiometer), suggesting that the CERES calibration must be considered a possible source of the discrepancy.
Keywords: Antarktis; atmosfæren; fjernmåling; meteorologi; observasjoner; solstråling

Antarctic clouds - Lachlan-Cope, Tom (Polar Research, 2010)
Sensitivity studies with global climate models show that, by their influence on the radiation balance, Antarctic clouds play a major role in the climate system, both directly at high southern latitudes and indirectly globally, as the local circulation changes lead to global teleconnections. Unfortunately, observations of cloud distribution in the Antarctic are limited and often of low quality because of the practical difficulty in observing clouds in the harsh Antarctic environment. The best surface observations suggest that the fractional cloud cover at the South Pole is around 50–60% in all seasons, whereas the cloud cover rises to around 80–90% close to the coast of the continent. Microphysical observations of cloud parameters are also very sparse in the Antarctic. However, the few measurements that do exist show predominantly ice-crystal clouds across the interior, with mixed-phase clouds close to the coasts. Crystal sizes vary from 5 to 30 mm (effective radius) in the interior to somewhat larger ice crystals and water drops near the coast. A wide range of crystal shapes is observed at all sites. This review considers the available cloud observations and highlights the importance of Antarctic clouds and the need for better observations in the future.
Keywords: Antarktis; klimatologi; meteorologi; observasjoner; satellitt bilder; skyer

An observation of the banded structure of the Antarctic Coastal Current at the prime meridian - Núñez-Riboni, Ismael; Fahrbach, Eberhard (Polar Research, 2010)
Observations of three bands of westward flow and two countercurrents, spanning roughly 50 km from the ice-shelf edge in front of the Fimbul Ice Shelf (prime meridian) in Antarctica, are presented. A comparison with a numerical model and the proximity of two of these current cores to the ice shelf suggest that they split from the Antarctic Coastal Current because of the influence of sea ice on the surface drag. A comparison with previous studies suggests that the other core is the current associated with the Antarctic Slope Front. Because the Fimbul ice shelf overhangs the continental shelf, the Antarctic Coastal Current displaces offshore, getting close to the Antarctic Slope Front. The obtained structure is derived from conductivity–temperature–depth geostrophic velocities from February 2005, referenced with detided acoustic Doppler current profiler velocities.
Keywords: Sørishavet; geostrofisk; havis; havstrømmer; hydrografi; kyststrøm; meteorologi; sjøis

An extreme precipitation event in Dronning Maud Land, Antarctica: a case study with the Antarctic Mesoscale Prediction System - Schlosser, Elisabeth; Powers, Jordan G.; Duda, Michael G.; Manning, Kevin W.; Reijmer, Carleen H.; van den Broeke, Michiel R. (Polar Research, 2010)
An extreme precipitation event that influenced almost the whole polar plateau of Dronning Maud Land, Antarctica, is investigated using Antarctic Mesoscale Prediction System archive data. For the first time a high-resolution atmospheric model especially adapted for polar regions was used for such a study in Dronning Maud Land. The outstanding event of 21–25 February 2003 was connected to a strong north-westerly flow, caused by a blocking high above eastern Dronning Maud Land, that persisted for several days and brought unusually large levels of moisture to the Antarctic Plateau. This weather situation is most effective in bringing precipitation to high-altitude interior Antarctic ice-core drilling sites, where precipitation in the form of diamond dust usually dominates. However, a few such precipitation events per year can account for a large percentage of the annual accumulation, which can cause a strong bias in ice-core data. Additionally, increased temperatures and wind speeds during these events need to be taken into account for the correct climatic interpretation of ice cores. A better understanding of the frequency of occurrence of intermittent precipitation in the interior of Antarctica in past and future climates is necessary for both palaeoclimatological studies and estimates of future sea-level change.
Keywords: Dronning Maud Land; havnivåstigning; klimaendringer; klimatologi; meteorologi; nedbør; polarområdene